Polissacarídeos da alga marinha lithothamnion muelleri: obtenção, caracterização química e atividade antiartrítica - Bruna Gomes Malagoli (2012)
Marine organisms are a promising source of bioactive compounds, including red seaweeds, which are known to produce sulfated polysaccharides with different biological properties. The aim of this study was to obtain and characterize polysaccharide-rich fractions of the marine red alga Lithothamnion muelleri Lenormand ex Rosanoff (Hapalidiaceae), as well as to evaluate their anti-arthritic activity. The alga is commercialized as food supplement in Brazil in view of its mineral content. The algal material employed in the study was furnished by a brazilian company as a granulated powder. The mineral composition of the algal material was determined by ICP-AES and pointed out calcium (34.76±0.42%) and magnesium (2.71±0.07%) as major constituents. Polysaccharide-rich fractions were obtained by extraction of the algal material at 60 °C, for 2 hours, sequentially with 1% and 2% w/v Na2CO3 aqueous solution, affording fractions B1 and B2, respectively, followed by precipitation with ethanol (4:1 v/v) and dialysation of the precipitate against water in a cellulose membrane. Extraction yields ranged from 0.1034±0.0038 to 0.1296±0.0070% w/w. The fractions were submitted to size exclusion chromatography (Sephadex G-100), giving sub-fractions Fra B1 and Fra B2. The polysaccharide nature of B1, B2, Fra B1 and Fra B2 was characterized by chemical, chromatographic and spectroscopic methods, along with the presence of uronic acids and sulfate groups. The polysaccharides presented molecular weight in the range 43.01±4.26 to 60.70±4.90 kDa and uronic acid contents from 4.17±0.08 to 5.07±0.10%. Their composition was also characterized in terms of proteins (2.49±0.04 to 3.78±0.02%), total sugars (26.87±0.82 and 34.69±0.81%) and sulfate (8.94±0.25 to 11.70±0.21%) contents. The monosaccharide constituents were investigated in hydrolyzed samples of B1 and B2 by TLC on cellulose and GC-FID analyses, which disclosed a sulfated xylogalactan as the main polysaccharide of L. muelleri, with high contents also of glucose, mannose and glucuronic acid. The biological activity of L. muelleri, B1 and B2 was tested using a model of antigen-induced arthritis in C57BL/6 mice. The administration of L. muelleri (100 mg/kg), B1 (1 mg/kg) and B2 (1 mg/kg) per os, for 10 days, induced significant anti-inflammatory and anti-hypernociceptive response in the animals. All treatments reduced cell infiltration in the knee cavity and periarticular tissue. Besides, all treatments lowered cell adhesion in the vascular endothelium, as shown by intravital microscopy experiments. Histological analyses revealed smaller damages in the knee after treatment with the alga, B1 and B2. Calcium carbonate, the major mineral found in L. muelleri, did not induced anti-inflammatory activity, thus indicating that sulfated polysaccharides are responsible for the anti-arthritic effect of the species. In conclusion, the major polysaccharide of L. muelleri was isolated and chemically characterized, and its participation on the anti-arthritic activity of the alga has been demonstrated in vivo